POLIGAMI DAN KESENGSARAAN PEREMPUAN - SADNYINI, SH, I.A. (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 1 Januari 2007, 2012)
Since a long time ago women are struggle their rights exactly in the sector of wedding law that’s against a Poligamy in Indonesia, but it couldn’[t 100%, just Poligamy with tight condition would be allow, in spite of that condition often be forged, so that polygamy threatened a house life which to come to sorrow woman in their childs. That means failed a purpose of wedding that regulated in “UU No. 1 Tahun 1974” because that a whole women in Indonesia still struggle their rights especially against Poligamy.